Pengembangan Media Pembelajaran berbasis PowerPoint Interaktif pada Pelajaran IPAS Kelas V Sekolah Dasar - Sopiandi, Dede Ari; Emelia, Emelia; Silviana, Januarita Ulfa; Hasibuan, Putri Rahmadani (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2024)
This research is a research and development ( R&D) study which aims to develop an interactive Powerpoint-based science learning media with a focus on food webs and food chains in class V elementary schools. This research uses the ADDIE development model which consists of 5 stages, namely : Analyze, Design, Development, Implementation, and Evaluation. Data collection uses a validation questionnaire. The Interactive Powerpoint trial was carried out on 10 fifth grade elementary school students. Based on the data obtained from the results of the Interactive Powerpoint media trial, researchers obtained the results, namely first, 8 students said they had never learned using Interactive Powerpoint media, while 2 students said they had learned using Interactive Powerpoint media. Second, all 10 students said that the Interactive Powerpoint media was fun and not boring, so they were very enthusiastic and happy when learning using Interactive Powerpoint media. Third, 10 students said that this Interactive Powerpoint media helped them understand the subject matter and increased their interest in learning.